Risk management: some lessons from the credit crisis - Fishwick, Edward (Henry Stewart Talks, 2010)
Risk management, lessons from the credit crisis, The importance of liquidity, How Assumptions are just assumptions, Trailing 60 day correlation (Momentum & Value), 220 day cumulative returns to Barra factors, Garbage (or worse) in/Garbage (or worse) out, The quick change in sources of risk, The inability to cram for a crisis, How volatility is only half the story, US "Quality" (1973 to date), Active and average earnings yield broken by Junk / Quality